Health Status and Quality of Life in Adult Biliary Atresia Patients Surviving with Their Native Livers - Lind, Robert C.; de Vries, Willemien; Keyzer-Dekker, Claudia M. G.; Peeters, Paul M. J. G.; Verkade, Henkjan J.; Hoekstra-Weebers, Josette E. H. M.; van der Steeg, Alida F. W.; Hulscher, Jan B. F. (European Journal of Pediatric Surgery, 2015)
Introduction Gaining an insight into the quality of life (QOL) in long-term biliary atresia (BA) survivors is becoming more important. Identifying patients with limitations might make tailor made interventions possible. This is the first study investigating the health status (HS) and QOL in adults surviving BA with their native livers, and comparing them with healthy peers.Methods BA patients surviving with their native liver were identified in the Netherlands Study Group on Biliary Atresia Registry database. The RAND-36 and the World Health Organization Quality of Life assessment instrument-100 (WHOQOL-100) were used to measure HS and QOL, respectively. Correlation between the RAND-36 and WHOQOL-100 was also assessed. Hospital Anxiety and Depression Scale (HADS) and the Impact Event Scale (IES) were also completed.Results In total, 25 (83%) of the 30 eligible patients after Kasai portoenterostomy completed the questionnaires (median age 23.2 years). A lower perceived level of general health in HS was found as compared with the reference group and a higher score on the social domain was reported in QOL. Correlations between HS and QOL questionnaires were moderate to good. For the group, overall HADS and IES scores were good, though individual patients did score above the cutoff of both the questionnaires.Conclusion Adult BA patients surviving with their native liver have similar HS and QOL as compared with their healthy peers. RAND-36 and WHOQOL-100 questionnaires are not interchangeable, but complementary to assess the patients' outcomes. The overall scores did not point to increased levels of anxiety and depression. However, on an individual level, three and six patients had a score above the cutoff of the HADS subscales demonstrating clinically relevant levels of anxiety and depression, respectively.
Keywords: biliary atresia; quality of life; health status; adult; native liver